ScMO(BO3) (M = Ca and Cd): new Sc-based oxyborates featuring interesting edge-sharing sandwich-like chains and UV cut-off edges. Issue 43 (18th October 2017) - Ma, Ruru; Xu, Dongdong; Yang, Yun; Su, Xin; Lei, Binghua; Yang, Zhihua; Pan, Shilie
Abstract : Two new Sc-based oxyborates, ScMO(BO3 ) (M = Ca and Cd), have been synthesized, which possess interesting edge-sharing sandwich-like chains and UV cut-off edges. Abstract : Two new isostructural rare-earth oxyborates ScMO(BO3 ) (M = Ca and Cd) with a three-dimensional (3D) cationic framework and parallel arranged [BO3 ] triangles have been synthesized by the flux method. In the 3D cationic framework, an interesting sandwich-like basic building unit (BBU) is constructed by two ∞1[Ca(1)O4 ] 6− chains and two ∞1[Sc(1)O4 ] 5− chains. ScMO(BO3 ) melt incongruently, which shows that title compounds can be grown by the flux method. The UV cut-off edges for ScCaO(BO3 ) and ScCdO(BO3 ) are 230 and 249 nm, respectively. In addition, the first-principles calculations are performed to gain further insights into the relationship between the microscopic electronic structures and associated optical properties.